A self-emulsifying delivery system loaded with efavirenz: The case for flax-seed oil - Mazonde, Priveledge (Rhodes University, Faculty of Pharmacy, Pharmacy)
The feasibility of incorporating efavirenz (EFV), an antiretroviral agent against HIV into a lipid-based self-emulsifying drug delivery system (SEDDS) containing vegetable oils was investigated. EFV has poor aqueous solubility and is classified under the Biopharmaceutical Classification System (BCS) as a class II compound with highly permeability, its aqueous solubility is less than 10 mg/ml and is defined as a practically insoluble compound with a consequent poor bioavailability of approximately 40%, and erratic dissolution behaviour. SEDDS formulations have been shown to improve the aqueous solubility and consequently the bioavailability of BCS II compounds such as EFV. EFV is a first line antiviral agent used in combination with other agents in antiretroviral therapy (ART). Among the number of NNRTIs approved for use in HIV treatment, EFV is one of the most commonly prescribed drug. Statistical methods and Design of Experiments (DoE) using Response Surface Methodology (RSM), specifically a Central Composite Design (CCD), were used to facilitate the development of a reversed-phase high performance liquid chromatographic (HPLC) method for the quantitation of EFV during formulation product and process development studies. A rapid, accurate, precise and sensitive HPLC method with ultraviolet (UV) detection was developed, optimised and validated for the in-vitro analysis of EFV in a total run time under 10 minutes for the elution of both EFV and loratidine which was used as the internal standard (IS). The method was then successfully applied to the determination of EFV in commercially available tablets. Excipient screening was undertaken using solubility studies and revealed that EFV had highest solubility in flaxseed oil in comparison to soybean, macadamia, grapeseed, sunflower and olive oils. The non-ionic Tween® 80 and Span® 20 were selected as surfactant and co-surfactant, respectively with ethanol co-solvent as they exhibited improved miscibility with co-solvent. Pre-formulation studies were undertaken to investigate the compatibility of the API with excipients and to identify a nano-emulsion region and other emulsion types using pseudoternary phase diagrams. The phase behaviour of crude cold pressed flaxseed oil with the selected non-ionic surfactants revealed an area within pseudo-ternary phase diagrams for different surfactant-mixtures formed gels/semisolid structures which can be exploited for other drug delivery strategies that require such properties. Fourier transform infrared spectroscopy (FT-IR), powder x-ray diffraction (XRD) and Raman spectroscopy were used to identify and assess the compatibility of EFV with chosen excipients. 2 A reduction in the peak intensity was observed for EFV when combined with each hydrophobic/lipid excipient evaluated revealing that there was a marked reduction in the crystallinity of the EFV. A decrease in crystallinity in comparison with the bulk API may indicate that EFV were amorphous or sequestered in a molecular dispersion and exhibited an increased solubility for the molecule. Flaxseed oil was used as the oil phase in studies for the optimization of surfactant mixtures undertaken using DoE, specifically a D-optimal mixtures design with the flaxseed oil content set at 10% m/m was performed. Solutions from the desired optimization function were produced based on desirability and five nanoemulsion formulations were produced and characterized in terms of in vitro release of efavirenz, drug loading capacity, Zeta Potential, droplet sizes and polydispersity index (PDI). Kinetically stable nanoemulsions containing 10% m/m flaxseed oil were successfully manufactured and assessed. Droplet sizes ranged between 156 and 225 nm, Zeta Potential between −24 and −41 mV and all formulations were found to be monodisperse with polydispersity indices ≤ 0.487. SEDDS formulations of EFV in nano-sized carriers were developed and optimised, in vitro drug release varied with varying amounts of ethanol in the formulation producing formulations that exhibited differently modulated drug in-vitro release profiles that may be further manipulated for better performance and therapeutic outcomes in terms of solubility and possibly bioavailability of EFV when delivered using SEDDS rather than using tablets which in turn may lead to better therapeutic outcomes for patients with HIV.
Keywords: Drug delivery systems; Linseed oil; Antiretroviral agents; HIV (Viruses); Drug carriers (Pharmacy); Solubility; High performance liquid chromatography; Efavirenz